2012
DOI: 10.1016/j.nbd.2012.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Glut1 deficiency (G1D): Epilepsy and metabolic dysfunction in a mouse model of the most common human phenotype

Abstract: Brain glucose supplies most of the carbon required for acetyl-coenzyme A (acetyl-CoA) generation (an important step for myelin synthesis) and for neurotransmitter production via further metabolism of acetyl-CoA in the tricarboxylic acid (TCA) cycle. However, it is not known whether reduced brain glucose transporter type I (GLUT-1) activity, the hallmark of the GLUT-1 deficiency (G1D) syndrome, leads to acetyl-CoA, TCA or neurotransmitter depletion. This question is relevant because, in its most common form in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(118 citation statements)
references
References 62 publications
(90 reference statements)
7
108
0
1
Order By: Relevance
“…It has been reported that GLUT-1 deficiency induces reactive astrocytosis, 39 defined as an increase in the number and the size of cells expressing glial fibrillary acidic protein. 40 Reactive astrocytes that retain expression of glutamine synthetase are present in the brain of G1D mice, 14 consistent with a greater rate of glutamine synthesis from heptanoate in G1D relative to normal brain.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…It has been reported that GLUT-1 deficiency induces reactive astrocytosis, 39 defined as an increase in the number and the size of cells expressing glial fibrillary acidic protein. 40 Reactive astrocytes that retain expression of glutamine synthetase are present in the brain of G1D mice, 14 consistent with a greater rate of glutamine synthesis from heptanoate in G1D relative to normal brain.…”
Section: Discussionmentioning
confidence: 74%
“…**Po0.01,***Po0.001. normal, which correlates with the presence of reactive astrocytes with preserved expression of glutamine synthetase in the G1D brain, probably as a potential compensatory mechanism of glucose transporter deficiency in these cells, 14 No differences were identified in the levels of glutamate or GABA across animal groups. The concentration of succinate, fumarate, and malate was also equivalent between both animal groups.…”
Section: C-nuclear Magnetic Resonance Spectramentioning
confidence: 83%
See 1 more Smart Citation
“…Marin-Valencia et al have shown in a mouse GLUT-1-deficiency model that total blood ketone bodies were markedly increased with normal blood glucose concentrations in a non-fasting state. This implies that GLUT-1-deficiency mice exhibit ketosis that can constitute a metabolic adaptation (Marin-Valencia et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…metode kod bolesnika uočen poremećen metabolizam glukoze u kortikostrijatalnim putevima (Weber et al, 2008;Suls et al, 2008). Sa druge strane, eksperimenti vršeni na GLUT1-DS mišijem modelu (primenom antisense GLUT-1) pokazuju da se nivo dopamina i serotonin, kao i produkata njihovog metabolizma, u korteksu, talamusu i striatumu ne razlikuje u odnosu na kontrolne miševe (Marin Valencia et al, 2012).…”
Section: Molekularno Genetička Osnova Dyt18unclassified